Waḥdah al-Wujūd dan Pelestarian Alam: Kajian Tasauf Tentang Lingkungan Hidup - Wiwi Siti Sajaroh (ILMU USHULUDDIN, 2014)
This article explains a perspective of waḥda al-wujūd in creating the universe as a union which cannot be separated from the three connected elements: God, man and universe. Therefore, the adherents of waḥda al-wujūd conception, especially Ibn ‘Arabī, interprets the universe as a unison with God, in which this means that whoever ruins the universe, in fact he ruins God as well. Apart from waḥda al-wujūd perspective, this writing also describes other Sufi schools like illumination (ishrāqī), manifestation (tajallī), ḥikma muta‘āliyya, and atomistic, as a comparison towards waḥda al-wujūd school.